Peranan Motivasi Kerja, Lingkungan Kerja, Dan Pengalaman Kerja Terhadap Kinerja Karyawan Dinas Pendapatan Daerah Kabupaten Jember - Mohammad Rizky Zakaria; Sampeadi Sampeadi; Susanti Prasetyaningtyas (UPT Penerbitan Universitas Jember, 2018)
This study aimed to know and analyze: (1) the role of motivation work of the performance of employees department of local revenue of Jember District, (2) the role of work environment of the performance of employees department of local revenue of Jember District, (3) the role of work experiences of the performance of employees department of local revenue of Jember District, and (4) the role of motivation work, work environment, and work experiences of the performance of employees department of local revenue of Jember District. The approach of the research which used in this research was quantitative. The population department of local revenue of Jember District as much as 261 people. Sample used as many as 73 people and technique the sample collection uses the method purposive sampling. The method of analysis of the data used in this research was linear regression analysis multiple. The results of the testing of hypothesis done show that: (1) motivation work has a positive role in employee's performance department of local revenue of Jember District, (2) work environment has a positive role in employee's performance department of local revenue of Jember District, (3) work experience has a positive role in employee's performance department of local revenue of Jember District, (4) motivation work, work environment, and work experience has a positive role in employee's performance department of local revenue of Jember District. Keywords: Employee Performance, Work Environment, Motivation Work, Work Experience